2022
DOI: 10.1016/j.jaci.2021.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Targeting immunodominant Bet v 1 epitopes with monoclonal antibodies prevents the birch allergic response

Abstract: Bet v 1 REGN5714 REGN5713 REGN5715Targeting immunodominant Bet v 1 epitopes with monoclonal antibodies prevents the birch allergic responseBet v 1, major birch tree allergen; FcER1, human receptor for Fc-fragment of IgE; Ig, immunoglobulin; mAbs, monoclonal antibodies.Cryo-electron microscopy reveals a planar and roughly symmetrical complex formed by REGN5713/14/15 bound to Bet v 1 Activation of allergic signaling cascade by Bet v 1 in birch allergic subjects REGN5713/14/15 binds to immunodominant epitopes on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 64 publications
4
42
0
Order By: Relevance
“…21 In agreement with this, we observe cross-reactive binding of our Bet v 1 mAbs to structurally similar allergens from alder and hazel, as well as the major apple allergen, Mal d 1. 37 Following treatment with REGN5713/14/15, there was significant suppression of basophil responsiveness to alder (rAlng 1), hazel (rCor a 1) pollen extract, and apple (rMal d 1). These data are also consistent with the SPT results that showed that REGN5713/14/15 significantly reduced mean wheal diameter after SPT with alder pollen extract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 In agreement with this, we observe cross-reactive binding of our Bet v 1 mAbs to structurally similar allergens from alder and hazel, as well as the major apple allergen, Mal d 1. 37 Following treatment with REGN5713/14/15, there was significant suppression of basophil responsiveness to alder (rAlng 1), hazel (rCor a 1) pollen extract, and apple (rMal d 1). These data are also consistent with the SPT results that showed that REGN5713/14/15 significantly reduced mean wheal diameter after SPT with alder pollen extract.…”
Section: Discussionmentioning
confidence: 99%
“…REGN5713, REGN5714, and REGN5715 were shown to bind to homologous allergens in alder, hazel and hornbeam, while REGN5715 also bound to those in apple. 37 For the REGN5713/14/15 treatment group, there was an inverse correlation between the percentage change in TNSS AUC (0-1 hour) and EC50 for birch allergen on day 8 (r 5 20.71;…”
Section: Titration Sptmentioning
confidence: 92%
See 1 more Smart Citation
“…Dissociation rates that are determined independently from the concentration of injected reagents, were proven for all three nanobodies to be in the range of 10 −4 /s demonstrating equal dissociation rates reported for allergen-specific monoclonal antibodies. 18,20 Since those monoclonal antibodies were effective in proof-of-principle clinical studies, 19,21 our generated Bet v 1-specific nanobodies represent promising tools as well for prospective clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, studies have demonstrated that passively administered allergen-specific monoclonal antibodies comparably reduce allergic responses as those induced in the course of AIT if they are directed to or overlap with IgE epitopes. [18][19][20][21] These trials showed for the first time that passive immunization with allergenspecific IgG antibodies able to inhibit patients' IgE binding to major allergens is a rapid, effective, and well-tolerated treatment to reduce allergic inflammation. [18][19][20][21] Since the generation and identification of blocking monoclonal human or humanized antibodies are laborious and expensive, recombinant antibody fragments including nanobodies turned out to be attractive molecules extensively studied for diverse applications in the recent past.…”
Section: Introductionmentioning
confidence: 99%